Decreased incidence of gout in diabetic patients using pioglitazone. (10th October 2017) - Niu, Sheng-Wen; Chang, Kai-Ting; Lin, Hugo You-Hsien; Kuo, I-Ching; Chang, Yu-Han; Chen, Yu-Han; Hung, Chi-Chih; Chiu, Yi-Wen; Hwang, Shang-Jyh
Abstract: Objective: The incidence and prevalence of gout are increasing, but the management is poor. Considering the increased prevalence of gout in the diabetic population, this study evaluated the effects of pioglitazone, an insulin resistance inhibitor, on the incidence of gout in the diabetic population. Methods: We used data from the National Health Insurance program in Taiwan. The pioglitazone cohort contained 30 100 patients and each patient was age and sex matched with three non-pioglitazone users who were randomly selected from the diabetic population. Cox proportional hazards regression analysis was conducted to estimate the effects of pioglitazone on the incidence of gout in the diabetic population. Results: The incidence of gout was significantly lower in pioglitazone users than in non-pioglitazone users [adjusted hazard ratio (aHR) 0.81 (95% CI 0.78, 0.85)]. The HR for the incidence of gout was lower in both male [aHR 0.80 (95% CI 0.75, 0.85)] and female [aHR 0.83 (95% CI 0.78, 0.88)] pioglitazone users than in non-pioglitazone users. An analysis of three age groups (<40, 40–59 and ⩾60 years) revealed that the HRs of both the 40–59 years [aHR 0.78 (95% CI 0.73, 0.83)] and the ⩾60 years [aHR 0.85 (95% CI 0.80, 0.91)] age groups were significantly lower among pioglitazone users than non-pioglitazone users. Conclusion: Compared with the non-pioglitazone users, the incidence of gout in the diabetic population using pioglitazone was less.